2003
DOI: 10.1002/food.200390014
|View full text |Cite
|
Sign up to set email alerts
|

Production and physicochemical characterization of resistant starch type III derived from pea starch

Abstract: Smooth pea starch was used for the production of physiological important resistant starch type III. For reduction of the molecular weight of the starch, different strategies including enzymatic debranching and acid hydrolysis (lintnerization), were tested to obtain an optimal starting material for retrogradation. The resulting polymer chain lengths were analyzed by high-performance anion-exchange chromatography. Temperature regimes and starch concentrations in gel were optimized during the retrogradation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 18 publications
1
43
0
2
Order By: Relevance
“…This pattern resulted because the extrusion treatment led to starch depolymerisation and linear chains showing a higher tendency to form structures presenting low enzymatic digestibility. 36,37 Because the gelatinisation temperature of mango starch was 70 • C, the amylose content of mango starch was important in this pattern. The regression model fitted to the RS experimental results showed a good correlation coefficient (0.80):…”
Section: Resultsmentioning
confidence: 99%
“…This pattern resulted because the extrusion treatment led to starch depolymerisation and linear chains showing a higher tendency to form structures presenting low enzymatic digestibility. 36,37 Because the gelatinisation temperature of mango starch was 70 • C, the amylose content of mango starch was important in this pattern. The regression model fitted to the RS experimental results showed a good correlation coefficient (0.80):…”
Section: Resultsmentioning
confidence: 99%
“…The extrusion process increased the RS content to a maximum of 9.7%, compared with a low value of 1.1% for native starch. This pattern resulted because the extrusion treatment led to starch depolymerization and linear chains showing a higher tendency to form structures presenting low enzymatic digestibility [65,66]. Because the gelatinization temperature of this starch was 70°C, its amylose content was important in this pattern [4].…”
Section: Extrusionmentioning
confidence: 93%
“…4) linear glucans within the optimal range was demonstrated by Potocki-Veronese et al (2005) and Schmiedl et al (2000) using amylosucrase from Neisseria polysaccharea and sucrose as substrate; however no industrial production has been reported. Debranching of amylopectin rich starches is thus used as a more practicable alternative to achieving a near optimum glucan chain distribution for RS III formation (González-soto, Mora-Escobedo, Hernández-Sánchez, Sánchez-Rivera, & Bello Pérez, 2007;Lehmann, Jacobasch, & Schmiedl, 2002;Lehmann, Rössler, Schmiedl, & Jacobasch, 2003;Mutungi, Onyango, Jaros, Henle, & Rohm, 2009). Recovery and recrystallization of glucans was also shown to be enhanced by controlled treatment of native starch with mineral acids prior to debranching (Lehmann et al, 2003).…”
Section: Introductionmentioning
confidence: 96%